The water planet - Feather, Ralph M. (Glencoe/McGraw-Hill, 2002)
Contents of this book: Chapter 1: Nature of science: Exploring the depths of the water planet; Chapter 2: Freshwater at earth's surface; Chapter 3: Groundwater resources; Chapter 4: Ocean motion; Chapter 5: Oceanography